Jihad Konstitusi dan Rekonstruksi Indonesia Berkemajuan: Strategi Advokasi Hukum Muhammadiyah dalam Menghadapi Ekstraksi Eksploitatif Sumber Daya Alam di Era Neoliberalisme - Evi Dwi Hastri; Absori Absori (STIKes Ibnu Sina Ajibarang, 2026)
This study is motivated by the proliferation of regulations that facilitate the exploitative extraction of natural resources in Indonesia as a consequence of the penetration of neoliberal ideology, which deviates from the mandate of Article 33 of the 1945 Constitution of the Republic of Indonesia. The significance of this research lies in the strategic role of Muhammadiyah through the